STUDY OF THE PSYCHOEMOTIONAL STATE OF WOMEN WITH INDUCED PREGNANCY AGAINST THE BACKGROUND OF COVID-19 INFECTION (Conferencea, 2022)
To evaluate and study the features of the psycho-emotional state of women with a complicated course of induced pregnancy by COVID-19 infection.